Who Runs? Honesty and Self-Selection into Politics - Sebastian Fehrler; Urs Fischbacher; Maik Schneider (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We examine the incentives to self-select into politics. To this end, we set up a two-stage political competition model and test its key mechanisms in the lab. At the entry stage, potential candidates compete in a contest to become their party's nominee. At the election stage, the nominated candidates campaign by making non-binding promises to voters. Confirming the model's key predictions, we find that dishonest people over-proportionally self-select into the political race.
Keywords: C92; D71; D83; 330